Developing reservoir drought index and conducting copula-based frequency analysis for Lake Urmia basin in Iran - Sina Sadeghfam; Hadi Farmani; Rasoul Mirabbasi (Journal of Hydrology: Regional Studies)
Study region: This study investigates the hydrological drought applied to five reservoirs in the Lake Urmia basin in Iran, a region suffering from unsustainable water resource management. Study focus: The study develops the Standardized Reservoir Index (SRI) for analyzing reservoir droughts using the standardization technique. Also, the copula analysis was conducted to calculate joint probabilities and return periods of drought characteristics, i.e., duration and severity. The Standardized Precipitation Index (SPI) and SRI time series were analyzed with the Sustainability Index (SI) to capture the anthropogenic impact on drought exacerbation. New hydrological insights for the region: The results reveal a 7- to 9-month lag time to propagate from meteorological drought (SPI) to hydrological drought (SRI). A comparison of SPI and SRI shows a significant SI decrease between 2 % and 13 %, highlighting anthropogenic impacts on drought exacerbation. Examination of the precipitation trend using the modified Mann-Kendall test also shows an insignificant trend at the 5 % significance level. The copulas were fitted with high accuracy, with Nash Sutcliffe efficiency values between 0.9 and 1, and root mean square error below 0.16. The results indicate that, from the perspective of the OR state, exacerbated hydrological droughts are detectable in the investigated reservoirs. The average probability of occurrence was 42 % for meteorological droughts and 46 % for hydrological droughts, for different severity and duration values.